MANFAAT RUANG TERBUKA HIJAU BAGI MASYARAKAT PERKOTAAN DITINJAU DARI ASPEK SOSIAL EKONOMI KOTA BANDA ACEH - Yusmawar, .; Jamal, Abd (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2016)
This study aimed to analyze the benefits of open green space for urban communities in terms of social and economic aspects in Kota Banda Aceh. The samples in this study were 100 people around the green open space. The model used is a Qualitative Descriptive Analysis using the method of collecting data obtained directly from respondents through interviews and using a literature review on the results of research that has been done. The results showed that most people in urban areas say get the full impact of the benefits of green open spaces. Green open space is very influential for the society means that people can feel the benefits of green open space for urban communities in terms of social and economic aspects in Kota Banda Aceh, one of her people can feel the benefit of air, plants that clean, could increase household incomes and other facilities. Most other people say have not received the benefits of green open space for the community, because it does not take advantage of the resence of green open space for urban communities in terms of social and economic aspects in Kota Banda Aceh to improve welfare. Kota Banda Aceh Government expected to be able to increase the presence of green space, creating Kota Banda Aceh as the city center with the quality of a clean and healthy environment.Â Keywords: Green Open Space, Descriptive Qualitative, Social and Economic Aspects.Â